2016
DOI: 10.1016/j.quascirev.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Strontium isotope investigation of ungulate movement patterns on the Pleistocene Paleo-Agulhas Plain of the Greater Cape Floristic Region, South Africa

Abstract: Middle Stone Age sites located within the Greater Cape Floristic Region on the South African southern coast have material culture with early evidence for key modern human behaviors such as projectile weaponry, large animal hunting, and symbolic behavior. In order to interpret how and why these changes evolved, it is necessary to understand their ecological context as it has direct relevance to foraging behavior. During periods of lowered sea level, a largely flat and vast expanse of land existed south of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
73
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 101 publications
0
73
1
Order By: Relevance
“…The primary driver of Pleistocene change was the expansion and contraction of the Paleo-Agulhas Plain, which resulted in changes in the size and structure of resources based on that plain [67]. A key component of this model is that by the late Middle Pleistocene or early Upper Pleistocene humans had adopted a coastal adaptation on the south coast that relied to a large extent on shellfish resources which tend to be dense and predictable [38], and was supplemented by exploitation of the diverse geophyte plants and a migratory large mammal ecosystem on the Paleo-Agulhas Plain [49, 77, 78]. Because of the stable supply of predictable and dense resources, these regions may have been able to support human populations through glacial periods when other regions were not, however, a more robust investigation is required to hind cast changes in resource availabilities in response to glacial cycling [40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary driver of Pleistocene change was the expansion and contraction of the Paleo-Agulhas Plain, which resulted in changes in the size and structure of resources based on that plain [67]. A key component of this model is that by the late Middle Pleistocene or early Upper Pleistocene humans had adopted a coastal adaptation on the south coast that relied to a large extent on shellfish resources which tend to be dense and predictable [38], and was supplemented by exploitation of the diverse geophyte plants and a migratory large mammal ecosystem on the Paleo-Agulhas Plain [49, 77, 78]. Because of the stable supply of predictable and dense resources, these regions may have been able to support human populations through glacial periods when other regions were not, however, a more robust investigation is required to hind cast changes in resource availabilities in response to glacial cycling [40].…”
Section: Introductionmentioning
confidence: 99%
“…Based on benthic δO 18 records, MIS 5b and 5a were moderate interglacial periods; MIS 4 is a moderate glacial period with medium-low temperatures; and MIS 3 is a moderate return to near interglacial conditions with medium-high temperatures [33, 138]. At PP5-6, glacial cycling influenced distance to coastline [44, 139], the size of the Paleo-Agulhas plain and the presence of grazing ungulates [49] and C3 adapted animals [47], C3-C4 vegetation types [42], and raw material availability [113, 128], with trickle-down effects on hunter-gatherer economic decision-making and adaptation [67]. Table 1 summarizes the changing conditions at Pinnacle Point by MIS.…”
Section: Introductionmentioning
confidence: 99%
“…A strontium isotope analysis showed that these grazing species lived almost exclusively on the PalaeoAgulhas plain and did not venture inland in any significant manner. 9 An analysis of age at death data of fossil blue antelope is consistent with a seasonal migratory movement. 52 The emergence of the Palaeo-Agulhas Plain is strictly controlled by sea level and the position of resultant shorelines.…”
Section: Implications Of the Palaeoecology Of The Palaeo-agulhas Plainmentioning
confidence: 81%
“…Recent reviews of the palaeoecology of the Palaeo-Agulhas Plain can be found in Marean et al 8 and Copeland et al 9 The faunal composition of the Palaeo-Agulhas Plain was first revealed by publications on the fossil faunal remains from Nelson Bay Cave and Klasies River. 46,48 More recent publications of faunal assemblages from Blombos 47 and Pinnacle Point 45 have added to this body of data.…”
Section: Implications Of the Palaeoecology Of The Palaeo-agulhas Plainmentioning
confidence: 99%
See 1 more Smart Citation